Expression and Significances of Contactin-1 in Human Gastric Cancer. (31st March 2013) - Yu, Ji-Wei; Wu, Sheng-Hua; Lu, Rui-qi; Wu, Ju-gang; Ni, Xiao-Chun; Zhou, Gou-cai; Jiang, Hai-guang; Zheng, Lin-Hai; Li, Xiao-Qiang; Du, Guang-Ye; Jiang, Bo-Jian
Abstract : Background . This study aimed at determining the relationship between vascular endothelial growth factor-C (VEGF-C), vascular endothelial growth factor receptor-3 (VEGFR-3), and contactin-1 (CNTN-1) expression in gastric cancer (GC). Methods . The expression level of CNTN-1 mRNA and CNTN-1 protein of 33 cases was determined using RT-PCR and Western Blot. And 105 cases were immunohistochemically examined for VEGF-C, VEGFR-3, and CNTN-1 expressions. Assessment of lymphatic vessel density (LVD) was also performed by D2-40 immunostaining. Then we analyzed the relationships between VEGF-C, VEGFR-3, and CNTN-1, as well as their correlations with clinicopathologic features, LVD, and survival time. Results . The positivity rate of VEGF-C, VEGFR-3, and CNTN-1 in primary tumor was 56.19%, 64.76%, and 58.09%. The expression of CNTN-1 significantly correlated with VEGF-C (P < 0.001 ) and VEGFR-3 (P < 0.001 ). All of them were closely related to TNM stage, lymphatic invasion, and lymph node involvement (P < 0.05 ). LVD was significantly correlated with VEGF-C (P = 0.001 ), VEGFR-3 (P = 0.011 ), and CNTN-1 expression (P < 0.001 ). VEGF-C, VEGFR-3, and CNTN-1 expression significantly associated with poorer prognosis (P < 0.001, P = 0.034, P = 0.012, resp.). Conclusion . CNTN-1 associated with VEGF-C and VEGFR-3 expression in GC. All of them correlated with lymphatic metastasis, which might play an important role in the lymphatic invasion via lymphangiogenesis pathway in GC.